Relação entre o tempo de amamentação e a prevalência de mordidas cruzadas posteriores na dentadura decídua - Kobayashi, Henri Menezes (2007)
The aim of this study was to evaluate the relationship between breastfeeding and the prevalence of posterior crossbite in the primary dentition in Brazilian children. The sample comprised 1377 Brazilian children, of both genders, aged 3 to 6 years, enrolled in public schools located at the eastern region of São Paulo city. Questionnaires concerning breastfeeding were sent to their parents. Chi-square test, Student “t” test (p < 0.05) and relative risks (odds ratio) were used to evaluate the association between breastfeeding and the prevalence of posterior crossbite and also to determine relative risks for this maloccusion. The general prevalence of posterior crossbite was 16.6% and 2.8% for bilateral posterior crossbite, 4.4% for true unilateral posterior crossbite and 9.4% for unilateral posterior crossbite with mandibular functional deviation. Results showed a significant association between exclusive breastfeeding periods and the prevalence of posterior crossbite (p = 0.0000). Children that were never breastfed reveled a 19.94 higher risk the development of posterior crossbite when compared to children that were breastfed for more than 12 months and 4.96 higher risk when compared to children breastfed between 6 and 12 months.